Characterization of non-equilibrium nanoparticle adsorption on a model biological substrate - Park, Jung Jin (Langmuir : the ACS journal of surfaces and colloids, 2010)
The kinetics of nanoparticle (NP) adsorption on a model biological interface (collagen) is measured in microfluidic channels using surface plasmon resonance (SPR) imaging over a range of CdSe/ZnS quantum dot concentrations to investigate the underlying binding process. Spherical CdSe/ZnS core-shell NP, derivatized with 3-mercaptopropionic acid (3-MPA), were considered to be model NPs because of their widespread use in biological applications and their relatively monodisperse size. The kinetic adsorption data suggests that the binding between the NP and the collagen substrate is irreversible at room temperature (pH approximately 7.4), and this type of adsorption process was further characterized in the context of a surface absorption model. Specifically, diffusion-limited adsorption was found to predominate the adsorption process at lower concentrations (<0.4 micromol/L), and NP adsorption was reaction-limited at higher concentration (>0.4 micromol/L). A limited pH study of our system indicates that NPs desorb from collagen under acidic conditions (pH 5.5); no significant desorption was observed under neutral and basic pH conditions. These observations are consistent with electrostatic interactions being the dominant force governing NP desorption from collagen substrates. Our present methodology for characterizing the seemingly irreversible NP adsorption complements our earlier study where NP adsorption onto weakly adsorbing surfaces (self-assembled monolayers) was characterized by Langmuir NP adsorption measurements